Damage to the Old North Church after Hurricane Carol, August 25, 1954 - Unknown (Tufts Archival Research Center, 2005)
Street-level view looking southeast from Hull Street toward the Old North Church on Salem Street. Debris from the toppled steeple fills the street in front of the building. Three people are standing on the sidewalk on Hull Street on the right of the image looking toward the photographer. 8 1/2 x 6 1/2 Photographs